Experimental and analytical investigation of secondary current cells effects on hydraulic jump characteristics in trapezoidal channels / Investigación experimental y analítica de los efectos de las células secundarias actuales en las características del salto hidráulico en canales trapezoidales - Fatehi-Nobarian, Bahador; Hajikandi, Hooman; Hassanzadeh, Yousef; Jamali, Saeed (Tecnología y ciencias del agua, 2019)
Fluid dynamics aims at understanding the movement of liquids and gases by functions that describe the distribution of velocities. In the present study, the characteristics of secondary currents in trapezoidal channels with side angles of 45, 60 and 75° subjected to the influence of five different discharges with experimental tests, are investigated and the results are compared with that of Flow3D. The results obtained from experimental measurements and numerical models comparison of the rate of secondary currents in different Froude numbers demonstrated that there exists an opposite relationship between the secondary velocity in the direction of perpendicular to the axis of flows (Vx) and velocity in a direction perpendicular to the flow level (Vz) in trapezoidal channels. Moreover, at 45° angle, there has been a remarkable energy loss during hydraulic jump. The ratio of the increase in the secondary currents velocity in X direction in Froude number 10 of 45° angle is higher than that of two other sections, which is equal to 71%, compared to 75° angle in numerical models and in Froude number 9 it was 91% during experimental tests. Then, the secondary currents velocity in Z direction for Froude number 2 of 75° angle is higher than that of two other sections, which is 88%, compared to the 45° angle in numerical models and in Froude number 1.5 it was equal to 74.5% for experimental tests.